Neurocognitive performance and mental health of retired female football players compared to non-contact sport athletes. Issue 1 (3rd December 2020) - Prien, Annika; Feddermann-Demont, Nina; Verhagen, Evert; Twisk, Jos; Junge, Astrid
Abstract : Background: Adverse long-term effects of playing football due to repetitive head impact exposure on neurocognition and mental health are controversial. To date, no studies have evaluated such effects in women. Aims: To (1) compare neurocognitive performance, cognitive symptoms and mental health in retired elite female football players (FB) with retired elite female non-contact sport athletes (CON), and to (2) assess whether findings are related to history of concussion and/or heading exposure in FB. Methods: Neurocognitive performance, mental health and cognitive symptoms were assessed using computerised tests (CNS-vital signs), paper pen tests (Category fluency, Trail-Making Test, Digit Span, Paced Auditory Serial Addition Test), questionnaires (Hospital Anxiety and Depression Scale, SF-36v2 Health Survey) and a symptom checklist. Heading exposure and concussion history were self-reported in an online survey and in a clinical interview, respectively. Linear regression was used to analyse the effect of football, concussion and heading exposure on outcomes adjusted for confounders. Results: FB (n=66) performed similar to CON (n=45) on neurocognitive tests, except for significantly lower scores on verbal memory (mean difference (MD)=−7.038, 95% CI −12.98 to –0.08, p=0.038) and verbal fluency tests (MD=−7.534, 95% CI –13.75 to –0.46, p=0.016). Among FB weaker verbal fluency performance was significantly associated with ≥2 concussions (MD=−10.36, 95% CI –18.48 to –2.83, p=0.017), and weaker verbal memory performance with frequent heading (MD=−9.166, 95% CI –17.59 to –0.123, p=0.041). The depression score differed significantly between study populations, and was significantly associated with frequent heading but not with history of concussion in FB. Conclusion: Further studies should investigate the clinical relevance of our findings and whether the observed associations point to a causal link between repetitive head impacts and verbal memory/fluency or mental health.